COVID-19: Scientific Arguments, Denialism, Eugenics, and the Construction of the Antisocial Distancing Discourse in Brazil - Malinverni, Claudia; Brigagão, Jacqueline Isaac Machado (Frontiers in Communication, 2020)
Since March 11, the world has been experiencing a pandemic of Sars-Cov-2, the new coronavirus, which emerged in China in late December 2019 and causes the COVID-19 disease. Pandemics are characterized by pathogen´s ability of emerging or re-emerging across geographical boundaries, simultaneously affecting a large number of people around the world, due to the sustained transmission in humans. In the case of the COVID-19 pandemic, we have witnessed in real time the dissemination of different types of information about it and strategies used to contain the rate of virus contamination. Our main goal in this study is to analyze the discursive production of the Brazilian journalistic media about vertical isolation as a supposed scientific strategy, and to demonstrate how that has been used in the denialist approach adopted by the Brazilian President Jair Bolsonaro. The research was carried out on the Google platform, using the following descriptors: coronavirus and herd immunity; coronavirus and the Imperial College herd immunity strategy; vertical isolation; Bolsonaro and vertical isolation. 36 articles were selected for a qualitative analysis besides the original article by David L. Katz (published in The New York Times), where he claims the creation of the vertical confinement strategy. All documents of the analytical corpus are open and free of charge. The articles were submitted to discursive analysis and the main results shows that Brazilian media highlighted Bolsonaro´s proposal of vertical isolation and amplified his pandemic denial and eugenics policies The mass media vehicles play a central role in the dissemination of information and should commit to the publication of reliable and trustworthy information, as well as to objectively situate the areas of knowledge of the specialists whose opinions are being published